Caregiver Satisfaction with a Video Telehealth Home Safety Evaluation for Dementia - Megan E. Gately; Linda Tickle-Degnen; Scott A. Trudeau; Nathan Ward; Keren Ladin; Lauren R. Moo (International Journal of Telerehabilitation)
Family caregivers are vital to telehealth-delivered dementia care. The objective of this mixed methods descriptive study conducted in the VA Bedford Healthcare System was to examine caregiver satisfaction with a video telehealth dementia home safety occupational therapy evaluation. Ten caregivers of Veterans with dementia participated. Ratings of caregiver satisfaction, measured by nine Likert scale items including ability to see and hear, were examined in relation to person and visit-related contextual factors extracted from RA field notes, to develop an in-depth understanding of caregiver experience. Person factors included caregiver age and gender and Veteran cognitive status. Visit-related contextual factors included occurrence  of technical glitches. Caregiver visit satisfaction was overall positive, with exceptions related to technological glitches and the presence of the person with dementia during the visit. Veteran cognitive status appeared to influence caregiver satisfaction. Implications of the study are that proactively addressing technical glitches and incorporating dementia stage-specific approaches may optimize caregivers’ telehealth experience.